The Use of Social Media Application as a Factor Influencing the Students' Decisions-Making to Enrol at Private Higher Education Institutions using Smart PLS - Aeshah Mohd Ali; Mohd Farid Shamsudin; Aina Mohd Ali; Mohd Fikri Ishak; Siti Aisyah Esa (Journal of Information Technology Management, 2021)
This study assessed the use of social media application significantly influence the students' decision-making to enrol at private higher education institutions (HEIs) within the Malaysian context. The underpinning theory applied in this study was the Theory of Reasoned Action (TRA). A quantitative method, stratified sampling technique and systematic sampling technique applied in this study to test the proposed hypotheses based on a sample of 500 first-year students in their first academic semester at 23 selected private HEIs in Kuala Lumpur and Selangor. Data analysis was carried out using smartPLS software. The analysis outcome of the focal study had expounded a significant positive relationship between the use of social media application and students' decision-making as a direct relationship. Thus, analysis of the structural model had further verified that hypotheses h1 of the focal study were accepted. The result shows a  significant positive relationship between social media application and students' decision-making indicated by a path coefficient of  0.630, t-value of 24.103, and p-value of 0.000.